Becoming a Research Practitioner: A meta-synthesis - Bager-Charleson, Sofie; du Plock, Simon; McBeath, Alistair; Adams, Marie (European Journal for Qualitative Research in Psychotherapy, 2020)
Mental health and emotional wellbeing are notoriously difficult to research and understand.Psychotherapy plays a significant role in generating new knowledge in the field. This study offers a metasynthesis of earlier published, primary research reports into therapists’ experience of and involvement in postgraduate research. Meta-synthesis is an approach of synthesising findings from different studies to enable deeper understanding about a research topic. The synthesis involved ‘re-searching’ and reviewing three studies previously published by the authors in response to an upcoming conference about postgraduate research with a new, transdisciplinary audience focusing on identity, access and opportunitywhen transitioning to postgraduate research. Our meta-synthesis followed three analytic phases, namely revisiting and reviewing the original findings (meta–data analysis), considering the original methods (metamethod and metatheory phase) and discussing, comparing and contrasting the primary research to create understandings (the synthesis phase). The new interpretations highlighted a loss of self, a repositioning or attempt to understand self in new contexts, and a newly emerging, integrated (transformed) sense of self across personal, professional, and educational contexts. The synthesis suggests further that researchers in the field of therapy often are particularly disadvantaged in terms of having few professional research opportunities and limited access to academic journals. Our synthesis highlights room for improvement in postgraduate research to support diversity, access, and opportunity.